The kinematics of curve skating for Japanese roller speed skaters in the 300-m time trial race - Okabe, F.; Takao, C.; Fujita, Z.; Tsuchiya, J. (The Japan Journal of Coaching Studies, 2019)
The study aimed to investigate the kinematics of curve skating among national-level Japanese roller speed skaters and world-class skaters in the 300-m time-trial race. The subjects were 12 finalists who were classified as world-class skaters (age, 24.9±4.1 years, height, 177.0±6.0 cm, weight, 73.0±5.2 kg) and 3 Japanese skaters (age, 18.7±0.5 years, height, 169.0±0.0 cm, weight, 64.3±3.1 kg) in the World Roller Speed Skating Championships in 2016. Data on the three-dimensional coordinates were calculated using the direct linear transformation technique. Parameters included the displacement of distance between the center of curvature and the center of body mass at the end and start of stroke, the skating length, speed, the stroke frequency, time in the one- and dual-leg supporting phase, side tilt angle, and segment angle. This study found the following: Japanese skaters (1) glided while climbing the incline owing to their low stroke frequency; therefore, their skating velocity additionally decreased; (2) were unable to control their center of body mass (COM) because they tilted their left shank less inward in the first half of the left stroke, (3) performed larger push-off movements in the duration of the dual-leg supporting phase in both strokes; and (4) restrained their COM as they tilted their shank less forward after tilting backward in both strokes; therefore, their skating velocity in the skating direction was lower.